BUDGET USE SYSTEM IN IMPLEMENTING WORK PROGRAM IN THE WATER FIELD OF THE PUBLIC WORKS OFFICE OF BARRU DISTRICT - Muhammad Ishak Ismail, Andi; Muhammad, Mukmin; Selvia, Ana (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal